Bipolar Camouflage: A Cerebellar Cognitive Affective Syndrome Case Report - Teresa Reynolds de Sousa; Miguel Schön; Pedro Alves; Filipa Novais; Tiago Mendes (Acta Médica Portuguesa, 2024)
The cerebellar cognitive affective syndrome is a neuropsychiatric syndrome composed of affective (anxiety, depression, euphoria, and emotional lability) and cognitive symptoms (executive, attentional, and visuospatial deficits) that was described in the 1990s. We present the case of a 49-year-old woman with a history of an acute neurological episode at the age of 28, after which she reported a change in personality, brief and alternating periods of depression, hypomania, and mixed episodes, and cognitive impairment that had a major impact on her personal and occupational level of functioning. She was initially diagnosed with bipolar disorder, but a clinical, neuropsychological, and imaging re-evaluation prompted a diagnostic reconsideration in favor of a cerebellar cognitive affective syndrome. This enabled therapeutical and prognostic refinement. Here, we discuss the diagnostic challenges of this syndrome and the implications that an accurate diagnosis has for patients.